Influence of Methomyl and Salinity on the Freshwater Snail Physa venustula: Egestion, Movement, and Hydration Index - Daniel Elias; Jose Iannacone; Jason Doll; Janina Coripuna; Isabel Gonzalez; Alejandra I Herrera; Salvador Inzua; Isbeth I Luyo; Kimberly M Ñahuin; Jaime M Saavedra; Genesis Y Salazar; Giacomo Velasco; et al. (Tropical Life Sciences Research, 2025)
Human activities, particularly agriculture and urbanisation often have detrimental effects on aquatic ecosystems and their ecosystem services to varying degrees. Organic pollutants (e.g., pesticides, pharmaceuticals, Per- and Polyfluoroalkyl Substances [PFAS]) and abiotic stressors (e.g., salinity, temperature, pH) are common stressors of freshwater habitats with expanding platforms documenting these problems or issues. This research addresses the effects of individual and combined methomyl (insecticide) and elevated salinity on movement, hydration and egestion of the snail Physa venustula. Snails were exposed to treatment concentrations of 100 ?g/L of methomyl and 5 g/L salinity for 96 h. Results indicated a significant reduction in snail movement when exposed to salinity (74%), and in combination with methomyl (67%). In contrast, we did not observe significant effects on egestion or hydration across treatments. These findings suggest that there is an energy trade-off to maintain homeostasis from the other physiological processes. Reduced movement can alter feeding rates, predator avoidance behaviour leading to changes in ecosystem structure and function. This research can provide critical insight into how short-term exposure to multiple stressors affects freshwater invertebrates and suggest P. venustula may be useful for early detection of water quality changes, especially in regions where chemical monitoring is limited.